2011
DOI: 10.3945/jn.110.127118
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Arachidonate Differentially Alters Desaturase-Elongase Pathway Flux and Gene Expression in Liver and Intestine of Suckling Pigs,

Abstract: Because dietary arachidonate (ARA) and its eicosanoid derivatives are major regulators of intestinal homeostasis and repair following injury, we evaluated the effects of dietary ARA on desaturation and elongation of (13)C-18:2(n-6) and mRNA abundance of Δ-6-desaturase (FADS2), elongase (ELOVL5), and Δ-5-desaturase (FADS1) in liver and intestine. Day-old pigs (n = 96) were fed milk-based formula containing 0, 0.5, 2.5, or 5% ARA or 5% eicosapentaenoic acid of total fatty acids for 4, 8, and 16 d. In liver, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…FADS2 catalyses the initial desaturation step of α-linolenic acid (C18:3) and linoleic acid (C18:2) in the enzyme cascade that ultimately leads, via FADS1 , to synthesis of the long chain polyunsaturated fatty acids (LC-PUFAs) arachidonic acid (C20:4) and eicosapentaenoic acid (C20:5). Synthesis of LC-PUFAs arachidonic acid and eicosapentaenoic acid mainly occurs in the liver and adipose [30] and suppression of their synthesis in SNEB cows may contribute to the poor fertility in high-yielding dairy herds. It was recently reported that polymorphisms in FADS1 and FADS2 were associated with reduced serum arachidonic levels in humans [31].…”
Section: Resultsmentioning
confidence: 99%
“…FADS2 catalyses the initial desaturation step of α-linolenic acid (C18:3) and linoleic acid (C18:2) in the enzyme cascade that ultimately leads, via FADS1 , to synthesis of the long chain polyunsaturated fatty acids (LC-PUFAs) arachidonic acid (C20:4) and eicosapentaenoic acid (C20:5). Synthesis of LC-PUFAs arachidonic acid and eicosapentaenoic acid mainly occurs in the liver and adipose [30] and suppression of their synthesis in SNEB cows may contribute to the poor fertility in high-yielding dairy herds. It was recently reported that polymorphisms in FADS1 and FADS2 were associated with reduced serum arachidonic levels in humans [31].…”
Section: Resultsmentioning
confidence: 99%
“…Among long-chain PUFA, arachidonic aicd is of particular importance because it is the major regulators of intestinal homeostasis and repair following injury, gastrointestial disturbances rank among the leading cause of neonatal morbidity, and mortality [17]. And research showed that desaturation to 13 C-18:3(N-6) increased linearly in pigs fed arachidonate but the alternate elongation to 13 C-20:2(n-6) was markedly elevated in pigs fed 0% arachinonate [17]. And on the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…However, LC-PUFA regulation of Fads gene products during the early postnatal period, when the demand for LC-PUFA is very high, has not been well studied. Recently Jacobi et al [16] showed that in suckling piglets, ARA intake at supra-physiological levels failed to down-regulate Fads2 or Fads1 in liver and actually increased their expression and LC-PUFA flux in intestine, providing evidence that dietary LC-PUFA may regulate Fads gene differently during early development. Less is known on the molecular regulation of Fads3 gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…The suckling piglet provides a practical mode for human infant development because the metabolic responses and the genetics of fatty acid desaturases in piglets are similar to those in humans [16, 20]. Thus, this study used the neonatal piglet model to investigate molecular determinants of FADS gene expression during early development.…”
Section: Introductionmentioning
confidence: 99%